Solutions of the Diophantine Equations Br=Js+Jt and Cr=Js+Jt - Ahmed Gaber; Mohiedeen Ahmed (Journal of Mathematics)
Let Brr≥0, Jrr≥0, and Crr≥0 be the balancing, Jacobsthal, and Lucas balancing numbers, respectively. In this paper, the diophantine equations Br=Js+Jt and Cr=Js+Jt are completely solved. The solutions rely basically on Matveev’s theorem on linear forms in logarithms of algebraic numbers and a procedure of reducing the upper bound due to Dujella and Pethö.